Effective Coping with Academic Stress Is a Matter of Personality Types: Revisiting the Person-Centred Approach - Cristina Varo; María del Mar Aires-González; María García-Jiménez; María Eva Trigo; Francisco Javier Cano-García (Behavioral Sciences, 2023)
Recent literature provides alarming data on the increase in university academic stress. The role of personality in understanding and addressing this problem is well established. However, this evidence could be improved by adopting a person-centred approach (e.g., types), as opposed to the usual variable-centred approach (e.g., traits), and considering the role of gender. Our aim was to explore how personality types and gender relate to coping strategies and perceived coping efficacy for academic stress. A total of 810 university psychology students completed the NEO-FFI Inventory and the Coping Strategies Inventory. Post hoc tests for MANOVA and ANOVA were performed. Types and gender were used as predictors and coping strategies, and perceived coping efficacy as criteria. There was no type-gender interaction. Types combining low neuroticism-high conscientiousness (e.g., entrepreneur) chose the most adaptive coping strategies and showed the highest levels of perceived coping efficacy, while high neuroticism-low conscientiousness types (e.g., insecure) opted for maladaptive coping strategies and presented the lowest perceived coping efficacy. Gender was not associated with perceived coping efficacy but with use (e.g., women prefer emotional expression). The personality typology provided useful information on individual differences in coping with academic stress, which can help guide specific strategies to manage it.